Brain targeting based nanocarriers loaded with resveratrol in Alzheimer's disease: A review - Cyrus Jalili; Amir Kiani; Mohammadreza Gholami; Fariborz Bahrehmand; Sajad Fakhri; Somayeh Kakehbaraei; Seyran Kakebaraei (IET Nanobiotechnology)
Abstract Alzheimer's disease (AD) is one of the chief neurological difficulties in the aged population, identified through dementia, memory disturbance, and reduced cognitive abilities. β‐amyloid (Aβ) plaques aggregations, generation of reactive oxygen species, and mitochondrial dysfunction are among the major signs of AD. Regarding the urgent need for the development of novel treatments for neurodegenerative diseases, researchers have recently perused the function of natural phytobioactive combinations, such as resveratrol (RES), in vivo and in vitro (animal models of AD). Investigations have shown the neuroprotective action of RES. This compound can be encapsulated by several methods (e.g. polymeric nanoparticles (NPs), solid lipid nanoparticles, Micelles, and liposomes). This antioxidant compound, however, barely crosses the blood–brain barrier (BBB), thereby limiting its bioavailability and stability at the target sites in the brain. Thanks to nanotechnology, the efficiency of AD therapy can be improved by encapsulating the drugs in a NP with a controlled size (1–100 nm). This article addressed the use of RES, as a Phytobioactive compound, to decrease the oxidative stress. Encapsulation of this compound in the form of nanocarriers to treat neurological diseases to improve BBB crossing is also discussed.